Makrofungi Diversity In The Sesaot Aik Nyet Forest Area, Buwun True Village, West Lombok, West Nusa Tenggara - Liza Fitriani; Cantika Agustina; Huru’in; Erlin Apriani; Firman Ali Rahman; Meilinda Pahriana Sulastri; Mai Rizali (Ecobios Journal Of Environmental Science, 2024)
This research aims to map and identify the types of macrofungi that exist in the Sesaot forest, understand the ecological role played by macrofungi in maintaining the balance of the forest ecosystem, and provide recommendations on sustainable forest management practices. The activity method can be referred to as "Macrofungi Field Survey" . This method involves direct observation in the field to search for, identify and record various types of macrofungi in the environment. The diversity of macrofungi in the Sesaot forest area, Aik Nyet Hamlet, Buwun Sejati Village, West Lombok, West Nusa Tenggara shows significant variation and represents the high richness of the ecosystem in the region. Studies carried out in this area identified various species of macrofungi distributed in a variety of forest habitats, from damp forest floors to dead tree trunks. Macrofungi are an important part of the biodiversity in forest ecosystems. Macrofungi diversity includes many species with various forms ranging from size, color and ecological function. Macrofungi also have a big role, namely as decomposers which help decompose organic matter, develop nutrients into the soil, and establish symbiotic relationships with other plants through microbes.